2022
DOI: 10.3390/jpm12101638
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Management of Severely Calcified Coronary Lesions

Abstract: Coronary artery calcification is increasingly prevalent in our patient population. It significantly limits the procedural success of percutaneous coronary intervention and is associated with a higher risk of adverse cardiovascular events both in the short-term and long-term. There are several modalities for modifying calcified plaque, such as balloon angioplasty (including specialty balloons), coronary atheroablative therapy (rotational, orbital, and laser atherectomy), and intravascular lithotripsy. We discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 90 publications
(95 reference statements)
0
9
0
2
Order By: Relevance
“…Em três anos de evolução, a ocorrência de eventos incluindo mortalidade por todas as causas, morte cardíaca e infarto agudo do miocárdio e desfecho composto de morte, infarto e nova revascularização, foram significativamente mais frequentes em pacientes com LCSC. [3][4][5] A análise de LCSC através de imagem intravascular, seja pelo USIC ou pela tomografia de coerência ótica (OCT), é indispensável para o seu correto manuseio. Tanto o USIC quanto a OCT podem identificar, localizar e quantificar o cálcio na artéria coronária, informações importantíssimas para a estratégia de preparo da lesão.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Em três anos de evolução, a ocorrência de eventos incluindo mortalidade por todas as causas, morte cardíaca e infarto agudo do miocárdio e desfecho composto de morte, infarto e nova revascularização, foram significativamente mais frequentes em pacientes com LCSC. [3][4][5] A análise de LCSC através de imagem intravascular, seja pelo USIC ou pela tomografia de coerência ótica (OCT), é indispensável para o seu correto manuseio. Tanto o USIC quanto a OCT podem identificar, localizar e quantificar o cálcio na artéria coronária, informações importantíssimas para a estratégia de preparo da lesão.…”
Section: Discussionunclassified
“…Existem scores validados para estimativa de subexpansão de stent e necessidade de modificação de placa. 4,5 As diretrizes de 2021 do American College of Cardiology/American Heart Association /Society for Cardiovascular Angiography and Interventions (ACC/AHA/SCAI) recomendam o uso de imagem em casos complexos (recomendação de Classe 2a, nível de evidência B). 6 Existem várias ferramentas utilizadas para modificação de placas severamente calcificadas: cateter-balão não complacente (BNC), balões de alta-pressão (HPB), cateter-balão com lâminas "cutting-balloon" (CB), aterectomia rotacional (AR), aterectomia orbital (AO), aterectomia a laser (AL) e mais recentemente a litotripsia intravascular coronária (IVL) (Figura 4).…”
Section: Discussionunclassified
“…According to the location distribution of calcification, calcified plaques can be divided into superficial calcification (located in the inner membrane and in contact with the lumen), deep calcification (near the junction of the media and outer membrane), and mixed calcification 7 . The IVUS calcification score (Figure S) indicated that both lesions with a calcification angle >270° and a length >5 mm, with a 360° annular calcification, with a reference vessel diameter ≤3.5 mm and with calcification nodules were given one point, respectively 8 . IVUS can provide sufficient spatial resolution, penetration depth, and real‐time vascular cross‐sectional images, 9 but ultrasonic waves are reflected by deposited calcium, accompanied by black sound shadows behind calcification.…”
Section: Invasive Imaging Diagnosis Methodsmentioning
confidence: 99%
“…An OCT scoring system (Figue S) was proposed to evaluate the severity of calcification lesions: There are two points for calcification angle >180° and one point for calcification angle 90–180°. The calcification thickness >0.5 mm is one point, and the calcification length >5 mm is one point 8 . OCT has a limited penetration capacity, but light can penetrate calcification without being reflected 1 .…”
Section: Invasive Imaging Diagnosis Methodsmentioning
confidence: 99%
See 1 more Smart Citation